APPLICATION OF THE INDEX CARD MATCH TYPE COOPERATIVE MODEL IN SOCIAL SCIENCE LEARNING IN PRIMARY SCHOOLS - _, Muhnar; _, Misnah; Ratu, Bau; _, Iskandar; _, Nurwahyuni; Elfira, Ninil (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2024)
Social studies subjects are integrated learning from history, geography and economics subjects as well as other science subjects so that the content is very large and the subject matter is very large and quite heavy. Thus, a learning model is needed that can motivate students in learning, especially social studies learning. This research aims to see the results of implementing the index card match type cooperative model in social studies learning in elementary schools. This research uses a qualitative approach and the type of research is classroom action research. The subjects of this research were teachers and students of class 5 at SDN 2 Bahonsuai, consisting of 22 students. This research was carried out in 2 cycles. Each cycle includes planning, implementation, observation and reflection stages. Data collection was carried out using observation, test and documentation techniques. Data were analyzed using qualitative data analysis techniques. The results of the first cycle of learning show that teacher activities are in the good category (B), student activities and learning outcomes are in the sufficient category (C). The learning results of cycle II show that teacher activities, student activities and learning outcomes are in the good category (B) so it can be concluded that the application of the index card match type cooperative learning model can improve the process and student learning outcomes in social studies content in class 5 of SDN 2 Bahonsuai.​